Implementation of the Islamic Boarding School Law in Pamekasan Regency: Analysis of Institutional Effectiveness and Independence - Intan Nur Aini; Makbul Romadhoni; Ach. Sofyan (Penerbit Hellow Pustaka, 2025)
This study examines the effectiveness of implementing Law Number 18 of 2019 on Islamic Boarding Schools (Pesantren) in Pamekasan Regency, Madura. The legislation marks significant state recognition of pesantren as autonomous Islamic educational institutions in terms of governance, curriculum development, and their religious and social functions. However, at the regional level, its implementation faces various normative and structural challenges. Employing a qualitative approach through a literature-based study, this research analyzes legal documents, government policies, and scholarly literature using a descriptive-analytical method. The analysis focuses on three key dimensions: the normative framework of the regulation, policy implementation, and the level of institutional autonomy of pesantren. Findings indicate that while the law provides a strong legal foundation, Pamekasan has established Regional Regulation Number 5 of 2022 concerning Facilities for Islamic Boarding School Education as a derivative instrument, though its effectiveness requires strengthened cross-sectoral coordination. Nevertheless, pesantren continue to demonstrate adaptive capacity by strengthening institutional autonomy and preserving Islamic values rooted in local traditions, reflecting potential for constructive synergy between national policy and local dynamics.